Pengembangan Media Pembelajaran Bahasa Arab Berbasis Video Animasi Interaktif untuk Siswa Madrasah Aliyah - Kurniawan Hamidi; Wan Jamaluddin; Koderi Koderi; Erlina Erlina (Departement of Mathematics Education, 2023)
The purpose of this research is to find out whether the development of interactive animation video-based learning media can help achieve the desired learning objectives. Measuring the feasibility of the media produced in an achievement. Measuring the effectiveness of interactive video media on the progress of class XI Language MAN I Bandar Lampung in enjoying learning Arabic. The research method used by researchers is the method of research and development (research and development). The development model used is the DDD-E development model. The model to be used is adjusted to the product to be developed. This research produced a product in the form of interactive animated video media to train students' Arabic language skills. The validation stage obtained the results of the feasibility of the media by 92.5%, the feasibility of the material was obtained by a percentage of 96.9%, the feasibility of the program was obtained by a percentage of 96.4%. Based on these results, interactive animated video media is feasible to use. The effectiveness test results obtained based on the results of the t test show the results of the Sig value from table .000 < than 0.05. The calculation results show Tcount > Ttable (74,061 > 2,021) then Ho is rejected so it can be concluded that interactive animated video media is effectively used in learning speaking skills. This shows that interactive animated videos are very well used in learning in the classroom, especially practicing speaking skills.